PENGARUH LINGKUNGAN KERJA, KESEHATAN DAN KESELAMATAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN (Studi pada karyawan bagian produksi PT. BERLINA Tbk Pandaan) - Anisah Fauziyah; Abdul Qodir Djaelani; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT               This  study  aims  to  know  and  analyze  the  influence  of  work  environment,  occupational  health  and  work   safety  on  work  productivity  of  production  employee.  Respondents  in  this  study  are  employess  of  production  at  PT.  Berlina  Tbk  Pandaan  Pasuruan.  Sample  of  research  as  many  as  90  employess  of  production  selected  by  method  Stratified  Proportional  Random  Sampling.  Type  of  research  using  quantitative  research  with  the  data  collection  method  used  is  distributing  questionnaires  and  interview.  Data  analysis  using  multiple  linear  regression  analysis  with  the  help  of  software  SPSS  14.0  for  windows.               The  results  showed  that  work  environment  variables  partially  has  an  influence  negativly  but  the  health  and  safety  variables  has  an  influence  positively  affect  the  work  productivity  of  production  employee  at  PT. Berlina  Tbk. And  simultaneously  work  environment,  occupational  health  and  safety  variables  Keywords : Work environment, Occupational Health and Safety, Work productivity